Procrastination and Online Exam Proctoring: Exam Anxiety and Exam Performance - Woldeab, Daniel; Brothen, Thomas; Barbu, Andreea (International Journal of E-Learning & Distance Education / Revue internationale de l’apprentissage en ligne et de l’enseignement à distance)

(untitled) (AU Press, 2025)
This study investigates academic procrastination in online exam proctoring environments, drawing on responses from 321 undergraduate students. It focuses on three key constructs: (1) the role of procrastination in online exam proctoring; (2) the impact of procrastination on performance in online proctored exams; and (3) the relationship between exam anxiety, procrastination, and online proctoring. The findings reveal: (1) a strong link between academic procrastination and poor performance in online proctored exams; (2) a significant correlation between procrastination and increased exam anxiety in online proctoring environments; and (3) that students who procrastinate have less favorable attitudes toward online exam proctoring.